LOAN (NPL), NET INTERST MARGIN (NIM) DAN GIRO WAJIB MINIMUM (GWM) TERHADAP LOAN TO DEPOSIT RATIO (LDR) - Agus Prastiono, 12.05.52.0079; Maryono, Maryono (Students' Journal of Accounting and Banking, 2016)
This study aims to determine the effect of CAR, NPL, NIM and the reserve requirement on LDR. The population in this study were banking companies listed in Indonesia Stock Exchange 2012-2014 year. The sample was taken by purposive sampling method. Data were analyzed using skewness-kurtosis normality test, classic assumption test, koofisien determinasi test, F test and test hypotheses. Results of testing hypothesis testing results first showed that the CAR significant positive effect on LDR, the results of testing the second hypothesiss hows that NPL significant positive effect on LDR, the results of testing the third hypothesisis obtained that the NIM effect significant positive effect on LDR, the fourth hypothesis testing results showed that GWM not significant effect on LDR.Keywords: CAR, NPL,NIM, GWM and LDR